ANALISIS RETRIBUSI PAJAK POTONG HEWAN RAMBU SOLO’ SEBAGAI PENDAPATAN DAERAH TORAJA UTARA - Titing, Alsa Mafrend; Mangopang, Asriyanti Dalame Ruru; Sanggalangi, Heslin Ngabar; Sabandar, Sita Yubelina; Sau, Arnold (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2025)
The research objectives include analyzing the levy collection and payment mechanisms, identifying socio-cultural-regulatory challenges, and assessing community acceptance and the role of Bapenda in supervision. The method used is a descriptive qualitative approach with a case study design, involving 9 key informants (Head of Bapenda, collection staff, Head of Lembang, Parenge' traditional leaders, and the community) selected through purposive sampling. Data were collected through in-depth interviews, field observations, and document studies, then analyzed interactively using the Miles-Huberman model. The research results reveal (1) a systematic ticket-based collection mechanism and Bapenda supervision; (2) crucial challenges, including community non-compliance, Perlem tariffs not synchronized with the Regional Regulation, and reliance on manual systems; (3) high community acceptance even though the burden is considered subjective; and (4) a dualistic (direct/indirect) oversight model. Theoretical implications confirm governance theory and reveal the dissonance between local and bureaucratic values, while practical implications recommend tariff harmonization, gradual digitalization, and a multi-stakeholder model such as Bapenda-Lembang-traditional leaders for the integration of fiscal policy and Toraja local wisdom.